DIGITALISASI SISTEM MANAJEMEN SISWA DI MADRASAH SEBAGAI INOVASI IDENTITAS ISLAM - fuad, Harisun; Imam wahyudi, Moh.; Sahara, Yudi; Rofiq, Ainur (As-Sulthan Journal of Education, 2024)
Digitalization in student management in madrasah is important for the development of Islamic identity, but it still requires the integration of religious values so as not to lose the spiritual essence of education. The purpose of this research is to mention the Digitalization of Student Management System in Madrasah as Islamic Identity Innovation. The object of research is the digitization of student management systems in madrasah as an innovation in Islamic identity at SMA Darussalam Blokagung. This research design uses qualitative research with a case study approach. Sources of informants in this study include the principal, teachers and students of SMA Darussalam Blokagung. Data collection techniques in this research are observation, interview, document. Data analysis in this study used Spradley's model by using four stages including domain analysis, taxonomy, compenential, and cultural themes. The results of this research Digitalization of Student Management System in Madrasah as an Innovation of Islamic Identity produced findings including the application of “Islamic Social Responsibility (ISR) tracker”, dynamic curriculum based on online platform with moral assessment & Islamic knowledge, and face recognition system with personal Islamic learning recommendations.